Analysis of Government Spending on Education on the HDI - Aan Riana; Muhammad Khafid (Universitas Negeri Semarang, 2022)
Human development indicates a country’s progress. It is used to achieve economic growth. The purpose of this study is to find out how the development of the human development index (HDI) in Central Java in 2016-2020 and to analyze how much influence government spending on education, poverty, population, growth rate, and the minimum wage has on the human development index (HDI) in central Java. The results indicate that government spending on education, population and growth rate, has no significant effect. The results of panel data regression indicate that government spending on education has a probability value of 0.0727, and poverty has a probability value of 0.000, which is smaller than 0.05. It means that poverty significantly affects the human development index. The number of the working-age population has a probability value of 0.2411, the growth rate has a probability value of 0.0538, and the minimum wage has a probability value of 0.000, which is smaller than 0.05. It means that the minimum wage significantly affects the Human development index.